Computers and geosciences teaching: study case at a private school from west zone of Rio de Janeiro - Bezerra, Hanna Priscila Alves; Firmino, Andressa Raiane de Souza; Barbosa, Jane Rangel Alves; Rodrigues, Ana Paula de Castro (Geosaberes; Vol 9 No 17 (2018): Jan - Apr, 2017)
The purpose of this work was to evaluate the relationship between teachers and students from the elementary school with geosciences and also the use of different didactical resources for geosciences teaching (Study case: Realengo, RJ). Specific questionnaires were applied to Geography/Biology teachers and students. Teachers affirmed that a link between geosciences and actual facts on media is made during classes, however rarely they diversify teaching resources; pointed out computing as the most used resource; and evaluated as low the interest of their students for biogeochemical cycles, clime, reliefs, land use and universe. Students pointed out computers as the most important source for school researches; few knew how to define geosciences, showing less interesting in it throughout the years. This fact could be a consequence of geosciences fragmentation in different disciplines.
Keywords: Geociências; Ensino; Recursos didáticos; Informática.